Selling from your comfort zone : the power of alignment marketing - Hall, Stacey, 1965- (Berrett-Koehler Publishers, 2022)
"Stacey Hall destroys the myth that salespeople must get out of their comfort zone to make a stellar sale by sharing a simple formula for a personalized approach to building collaboration and connection. So many salespeople "sell out" themselves and the products they represent because they are thrust far out of their comfort zone. Taking uncomfortable risks can produce anxiety, especially for women, which in turn affects the self-esteem and confidence that pushes them to achieve their goals. Studies reveal that while men generally rely on improving and driving outcomes to close sales, women tend to emphasize building connections, shaping solutions, and collaborating. Stacey Hall's alignment marketing formula combines both skillsets in an easy-to-follow process for gently expanding women's comfort zone so they can stay flexible and resilient in the face of problems and objections that all salespeople encounter along the way. Selling from Your Comfort Zone shifts away from "pushy" and "spammy" sales tactics and facilitates the gradual growth of people's comfort zone by helping them find alignment with their calling, personality traits, and core values"--